Genetically continuous populations of Striped Snakehead (Channa striata) in the Cingcingguling River fragmented by Sempor Reservoir, Central Java, Indonesia - NUNING SETYANINGRUM; W. LESTARI; KRISMONO KRISMONO; Agus Nuryanto (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Setyaningrum N, Lestari W, Nuryanto A. 2022. Genetically continuous populations of Striped Snakehead (Channa striata) in the Cingcingguling River fragmented by Sempor Reservoir, Central Java, Indonesia. Biodiversitas 23: 222-230. Cingcingguling River, located in Kebumen District, Central Java Province, Indonesia. The Sempor Reservoir fragments it. The previous study proved the negative impact of the reservoir on positive rheotaxis fish, mainly in genetic constituents between the reservoir and river populations. However, research has not been conducted on the negative rheotaxis fish, such as Channa striata. Assessing population genetic and taxonomic validity study of Striped Snakehead in the Cingcingguling River is an essential effort. Both studies could be done using the cytochrome c oxidase 1 gene. Therefore, this research aims to determine taxonomic status and evaluate the population genetic of C. striata in the Cingcingguling River. The samples were collected at eight sites, inside and outside the reservoir. The used marker was sequenced from 53 individuals, and all specimens showed high identity (98.67% to 100%) and low genetic distances (0.00 to 0.01) to C. striata (KU692421, KU852443, and MG438366). Those values proved that all samples were genetically identified as Channa striata. The vertical genetic distribution analysis demonstrated that C. striata populations are genetically not different along the river. Unlike rheotaxis positive fish phenomena, the reservoir's existence does not cause genetic fragmentation and leads to continuous striped snakehead populations.